Strategi Kepala Sekolah dalam Mengimplementasikan MBS di SMP Negeri 16 Purworejo - Siti Munawaroh (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2020)
The principal has a great responsibility in organizing educational activities. Therefore the principal is required to be able to manage the existing management in the institution he leads. However, the progress and decline of schools is not only influenced by the role of the school principal, but the results of the joint activities of various parties, including school committee officials. The school principal as an education manager is required to find and implement a new management strategy that can encourage quality improvement in schools. SBM is one of the government's efforts to achieve excellence in the nation's community in mastering science and technology. The aim of implementing SBM is to improve the quality of learning, curriculum, human resources and school services in general. This research seeks to reveal the principal's strategy in implementing SBM at SMP N 16 Purworejo. This research is a qualitative research. Data collection was carried out on research sources using interview, observation, and documentation techniques. The collected data is processed by data reduction activities, data presentation, and drawing conclusions. The data validity test was carried out using source triangulation techniques to ensure that the data obtained is valid. The results showed that the strategy used by the principal in implementing SBM at SMP N 16 Purworejo used the principles of autonomy, flexibility, participation and initiative. The principle of autonomy includes the principal's understanding of his role as an organizational leader who is independent and has autonomy in schools, teachers' understanding of changes in their role in SBM which affects the implementation of the learning process and the establishment of school programs, the understanding of school committee members of their role in managing schools according to the school's procedures manage MBS. The principle of flexibility includes the principal's understanding of his role as a flexible organizational leader, the teacher's understanding of the principal's flexibility in implementing SBM, the school committee's understanding of the principal's role as a flexible leader in implementing SBM. The principle of participation includes the participation of school principals and stakeholders, parents, teachers and administrative staff in decision making and other activities at school. Initiative principles include planning, curriculum management, process management such as teaching and learning activities, staff management, facility management, student services, school and community relations, school climate management, and evaluation.